2018
DOI: 10.1371/journal.pone.0209193
|View full text |Cite
|
Sign up to set email alerts
|

Late vertebral side effects in long-term survivors of irradiated childhood brain tumor

Abstract: PurposeLong-term side effects of the treatments are common in survivors of irradiated pediatric brain tumors. Ionizing radiation in combination with surgery and chemotherapy during childhood may reduce vertebral height and bone mineral density (BMD), and cause growth failure. The aim of this study was to evaluate the late consequences of tumor treatments on vertebrae in survivors of childhood brain tumors.Methods72 adult survivors (mean age 27.8 years, standard deviation 6.7) of irradiated childhood brain tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Indeed, chemotherapy has been shown to provide significant toxicities and adverse side effects ( 46 , 47 ). Similarly, radiotherapy induced many late side effects, especially for young patients, such as neurocognitive and neuroendocrine deficits, bone and soft tissue hypoplasia, and secondary benign or malignant tumors ( 47 , 48 ). The current challenge is to improve the survival rate of patients with pediatric brain tumors while minimizing the toxicity of these treatments.…”
Section: Pediatric Brain Tumorsmentioning
confidence: 99%
“…Indeed, chemotherapy has been shown to provide significant toxicities and adverse side effects ( 46 , 47 ). Similarly, radiotherapy induced many late side effects, especially for young patients, such as neurocognitive and neuroendocrine deficits, bone and soft tissue hypoplasia, and secondary benign or malignant tumors ( 47 , 48 ). The current challenge is to improve the survival rate of patients with pediatric brain tumors while minimizing the toxicity of these treatments.…”
Section: Pediatric Brain Tumorsmentioning
confidence: 99%
“…Linear growth stunting has been described previously in survivors of pediatric cancers with specific focus on the impact of radiation to the brain and spine on growth trajectories 41,42. At diagnosis, the patients diagnosed over 2 years of age had a higher mean HAZ compared with the youngest patients.…”
Section: Discussionmentioning
confidence: 76%
“…Shalet et al reported that radiation-induced growth impairment was observed in acute lymphoblastic leukemia (ALL) patients irradiated at younger ages [19]. Studies by Jussila et al [20] and Yu et al [21] suggested that young age at diagnosis were determined as a risk factor for growth impairment in brain malignancies. In consistent, our previous study revealed that 11.5 year.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible limitation is that the sitting heights of the pediatric patients were not included for analysis in this study. We were hence unable to estimate the deviation in stature attributable to impaired spinal growth caused by CSI [16,20]. Future longitudinal follow-up studies will focus on the comparisons between the cohort of pediatric patients with different doses of CSI such as NGGCTs and medulloblastoma, etc.…”
mentioning
confidence: 99%